Initial testing (stage 1) of eribulin, a novel tubulin binding agent, by the pediatric preclinical testing program. Issue 8 (28th March 2013) - Kolb, E. Anders; Gorlick, Richard; Reynolds, C. Patrick; Kang, Min H.; Carol, Hernan; Lock, Richard; Keir, Stephen T.; Maris, John M.; Billups, Catherine A.; DesJardins, Christopher; Kurmasheva, Raushan T.; Houghton, Peter J.; et al.
Abstract Background Antimitotic agents are essential components for curative therapy of pediatric acute leukemias and many solid tumors. Eribulin is a novel agent that differs from both Vinca alkaloids and taxanes in its mode of binding to tubulin polymers. Procedures Eribulin was tested against the PPTP in vitro cell line panel at concentrations from 0.1 nM to 1.0 μM and against the PPTP in vivo xenograft panels at a dose of 1 mg/kg (solid tumors) or 1.5 mg/kg (ALL models) using a q4dx3 schedule repeated at Day 21. Results In vitro eribulin demonstrated cytotoxic activity, with a median relative IC50 value of 0.27 nM, (range <0.1–14.8 nM). Eribulin was well tolerated in vivo, and all 43 xenograft models were considered evaluable for efficacy. Eribulin induced significant differences in event‐free survival (EFS) distribution compared to control in 29 of 35 (83%) of the solid tumors and in 8 of 8 (100%) of the ALL xenografts. Objective responses were observed in 18 of 35 (51%) solid tumor xenografts. Complete responses (CR) or maintained CR were observed in panels of Wilms tumor, Ewing sarcoma, rhabdomyosarcoma, glioblastoma, and osteosarcoma xenografts. All eight ALL xenografts achieved CR or MCR. Conclusions The high level of activity observed for eribulin against the PPTP preclinical models makes this an interesting agent to consider for pediatric evaluation. The activity pattern observed for eribulin in the solid tumor panels is equal or superior to that observed previously for vincristine. Pediatr Blood Cancer 2013;601325‐1332. © 2013 Wiley Periodicals, Inc.